PENGARUH DEBT TO ASSET RATIO (DAR) TERHADAP KUALITAS LABA PADA PT MULIA INDUSTRINDO,TBK - NUR ILAH; PUJI MUNIARTY (GANEC SWARA, 2024)
This research examines how the Debt to Asset Ratio (DAR) affects the profit quality of PT Mulia Industrindo, Tbk. This quantitative correlational type of research is used in the 2013–2022 financial reports, balance sheets, profit and loss reports, and cash flow reports. The sampling method uses purposive. SPSS v.20 software was used to analyze the relationship between Debt to Asset Ratio (DAR) and earnings quality using simple linear regression, correlation coefficient, coefficient of determination, and two-square t test. This research finds that the Debt to Asset Ratio (DAR) has no effect on earnings quality because the role of investors decreases if the company's assets are financed more by debt than by its own capital. Because this value fails to balance the capital available and needed in managing money.